2019
DOI: 10.1038/s41598-018-37183-5
|View full text |Cite
|
Sign up to set email alerts
|

Infant dietary patterns and early childhood caries in a multi-ethnic Asian cohort

Abstract: Dental caries, although preventable, remains one of the most prevalent chronic disease worldwide. Most studies focused on the relationship between sugar intake and caries. However, examining multidimensional dietary patterns is becoming increasingly important. Here, we examined the relationship between dietary patterns from ages 6 to 12 months and early childhood caries (ECC) at age 2 to 3-years. Infant dietary data was collected from caregivers and dietary pattern trajectories from 6 to 12 months derived. Ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 30 publications
3
32
1
Order By: Relevance
“…In the present study, the diversi ed pattern with a variety of food groups had high consumption of tubers, dairy products, bean and bean products, nut, dark leaf vegetables and fruits, meat and egg, and had higher rate of minimum dietary diversity and minimum acceptable diet assessing by World Health Organization infant and young child feeding indicators, corresponded to the guidelines or healthy pattern by previous studies [11,19]. The traditional pattern was characterized by high intake of cereals, water and soup, other vegetables and fruits, meat, and multi-nutrient powders, similar to the traditional Chinese adults dietary patterns [20][21][22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, the diversi ed pattern with a variety of food groups had high consumption of tubers, dairy products, bean and bean products, nut, dark leaf vegetables and fruits, meat and egg, and had higher rate of minimum dietary diversity and minimum acceptable diet assessing by World Health Organization infant and young child feeding indicators, corresponded to the guidelines or healthy pattern by previous studies [11,19]. The traditional pattern was characterized by high intake of cereals, water and soup, other vegetables and fruits, meat, and multi-nutrient powders, similar to the traditional Chinese adults dietary patterns [20][21][22].…”
Section: Discussionsupporting
confidence: 83%
“…The previous study from Singapore reported that four dietary patterns labeled Predominantly breast milk, Guidelines, Easy-to-prepare foods, and Noodles and seafood are observed among infant aged 6-to 12-months [9]. And other studies also shown that the dietary patterns among infants have association with weight [10], caries [11], bone mass [12], and intelligence quotient [13]. But few studies clari ed dietary patterns relate to anemia of infant.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring the relationship between dietary patterns and child obesity have shown inconsistent findings [20,21], while studies exploring the relationship between dietary patterns and ECC are rare. Those few studies which have investigated the latter relationship using a posteriori-derived indices have reported inconsistent findings [22,23] with only one study, to our knowledge, (and in an Asian multi-ethnic population), doing so using a priori-derived dietary patterns (exploratory factor analysis to examine diet trajectories between 6 and 12 months of age and ECC at ages 2 and 3 years) [24]. Such inconsistencies in the evidence may be due to discrepancies in the methodological approaches used to characterize dietary patterns (a priori vs. a posteriori).…”
Section: Introductionmentioning
confidence: 99%
“…Health Organization infant and young child feeding indicators, corresponded to the guidelines or healthy pattern by previous studies [11,16]. The traditional pattern was characterized by high intake of cereals, water and soup, other vegetables and fruits, meat, and multi-nutrient powders, similar to the traditional Chinese adults dietary patterns [17][18][19].…”
Section: Discussionmentioning
confidence: 62%
“…The previous study from Singapore had reported that four dietary patterns labeled Predominantly breast milk, Guidelines, Easy-to-prepare foods, and Noodles and seafood were observed infant aged 6-to 12-months [9]. And other studies also shown that the dietary patterns among infants had association with weight [10], caries [11], bone mass [12], and intelligence quotient [13]. But few studies clarified the dietary patterns related to anemia of infant.…”
mentioning
confidence: 99%